DETERMINATION OF UNIT COST AMONG SECONDARY SCHOOLS IN KENYA: A CASE OF NANDI NORTH DISTRICT, KENYA - Solomon Kipyego Ngetich; Benjamin Kyalo Wambua; Zachariah Kiptoo Kosgei (European Scientific Journal, ESJ, 2014)
This study determined unit costs of secondary schools in Nandi North District. It employed a descriptive survey design and was guided by a Cost Model derived from the General Education Production Function. Data was collected from all the Head teachers of public and private secondary schools in Nandi North District, Kenya. The research instruments used in collecting data were structured questionnaires. Analysis of data was done using both descriptive statistical techniques including percentages, means and frequency tables. It was found that a total of Ksh. 363,383,481 was spent for the entire district, translating into an average of Ksh. 8,863,012 per school or Ksh.41,768 per student. The school with the highest amount spent and the least amount spent was Ksh.31,332,348 and Ksh.1,586,940 respectively. The findings indicate that the average unit cost per district school was Ksh 34,849, whereas the average unit cost for the provincial schools was Ksh. 50,966. Private schools had an average of Ksh.35, 778 while public schools had an average of Ksh.43, 219. Mixed day schools incurred the least unit cost of Ksh. 33,309 and the highest unit cost was from boys boarding schools at Ksh.51,072. The study recommended that schools should prioritize expenditure areas such as acquisition of teaching and learning resources to ensure cost reduction. It is hoped that the findings from this study will be utilized by the Ministry of Education and other stakeholders in order to come up with strategies for reducing unit costs in schools and look for alternative sources of financing education in secondary schools in Nandi district.